Role of C-erbB2 expression in gallbladder cancer - Niraj Kumari; V K Kapoor; Narendra Krishnani; Kamlesh Kumar; Dinesh Kumar Baitha (Wolters Kluwer Medknow Publications, 2012)
Background: Gallbladder cancer (GBC) is a lethal malignancy presenting at an advanced stage. The pathogenesis is not well categorized, and surgery is the only treatment available at the early stage of the disease. There have been few reports on role of growth factor receptors in GBC. C-erbB2 is one such receptor whose over-expression is being explored in GBC as one of the factors involved in carcinogenesis and possible target for therapy. Materials and Methods: One hundred and four consecutive cases of GBC were retrospectively studied with regard to clinical features, histological type, grade and stage of tumor. Immunohistochemistry for C-erbB2 was done and expression was correlated with different clinic-pathological parameters and survival. Results: C-erbB2 overexpression was seen in 9.4% cases with complete staining and both complete and incomplete staining (2+ and 3+) was seen in 13.4% cases. Eighty percent of the C-erbB2 over-expressed cases were well differentiated and in stage II to stage IV disease. Dysplasia adjacent to carcinoma did not show any expression. No correlation was found with tumor grade, stage, gall stones, and patient survival. Xanthogranulomatous inflammation was inversely correlated with C-erbB2 over-expression. Median survival was 30 months in C-erbB2 over-expressed cases, and 12 months in C-erbB2 negative cases. Conclusion: We found complete membranous staining of C-erbB2 in 9.4% of GBC which was frequent in well differentiated and stage II to stage IV tumors. C-erbB2 tumors had longer median survival than C-erbB2 negative tumors. C-erbB2 is not involved early in the carcinogenetic process as none of the dysplasia showed expression. C-erbB2 over-expression may be considered as target for therapy in advanced stage of GBC.